Pengaruh Pengungkapan Pajak Dengan Agresivitas Pajak Sebagai Variabel Moderasi Pada Perusahaan LQ-45 - Thressy Anastasia Estralita Trisnawati (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
This study aims to determine the effect of Executive Compensation and Corporate Social Responsibility Disclosure on Tax Disclosure with Tax Aggressiveness as a mediation variable on LQ-45 companies listed on the Indonesia Stock Exchange during 2016-2019. Sample was selected using purposive sampling method and the valid data was 31 companies. Data processing techniques using multiple regression analysis what helped by SPSS program (Statistical Product and Service Solution) for Windows released 23 and SmartPLS version 3.3.2. The results of this study indicate that executive compensation has a negative and significant influence on tax disclosure while corporate social responsibility disclosure has not influence on tax disclosure, tax aggresiveness has not influence on tax disclosure, executive compensation has not influence on tax disclosure through tax aggresiveness and corporate social responsibility disclosure has not influence on tax disclosure through tax aggressiveness.